(3ef dG jMVQg Gdabjgs - (3Gdbej, CHh LYaQ, eMeO Hf Ydj Hf GdMSjf Hf ehSi Hf HGHhjg, J (B381 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B.. (3CHhGH GdbVGjG hGdCMcGe ; HGH eG jLhR GdJMGce Edjg hef dG jLhR , bGd CHh LYaQ (B...(3Qhi CMeO Hf YGFP (B((3YGHO(B) (3Yf CHj NOjLI SGde Hf ecqQe GdLqeGd bGd bGd CHh YHO Gddg LYaQ Hf eMeO GdUGOb Ydjg GdSdGe (B...s
(3BNQgG (B:s
.. (3heG cGf ajg Yf GdeYdi Hf eMeO GdHUQj abO QhjJg Yf CHj heMeO Hf GdMSf hLYaQ Hf eMeO Hf eSQhQ (B... (3Yf GdMSjf Hf eMeO Hf YGeQ Yf GdeYdi Hf eMeO GdHUQj heG cGf ajg Yf (B...(3hGdMeO ddgs
(3HChdg YbhO RhGL eJYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\ 274s
(3GdPQjYI (B22\6841s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis